System of radiation protection of the population after the accident at the Chernobyl NPP - ; Tsybulka, Mikalai; Germenchuk, Mariya (Journal of the Belarusian State University. Ecology, 2024)
The article describes international recommendations and radiation safety standards, the evolution of the formation of principles, criteria and the regulatory and methodological basis for radiation protection of the population of the Republic of Belarus after the accident at the Chernobyl nuclear power plant. A zoning scheme for the territory of Belarus subject to radioactive contamination is presented. The methodology for regulating the content of radionuclides in food products, the republican permissible levels of 137Cs and 90Sr in agricultural raw materials for processing for food purposes and feed for obtaining final products are outlined. In accordance with the legislation of Belarus, the residence and work of the population in the territory of radioactive contamination do not require any restrictions if the average annual effective radiation dose does not exceed 1 mSv per year above the level of natural and man-made radiation background. If the level exceeds 1 mSv per year, protective measures are taken. The permissible levels of 137Cs and 90Sr in food products were changed in accordance with the annual quotas for internal exposure and at different stages of the development of the post-accident situation were periodically revised towards tightening. The hygienic standard regulates the content of 137Cs in 14 groups of food products, the content of 90Sr in 10 groups. In order to ensure food production within reference levels, permissible levels of 137Cs and 90Sr in agricultural raw materials and feed have been developed. All crop and livestock products produced in areas contaminated with radionuclides and used for food purposes, processing, and sales on the domestic and foreign markets must comply with regulatory requirements.
Keywords: radiation protection; radiation doses; permissible and reference levels; food products; agricultural raw materials and feed